Mulberry based zinc nano-particles mitigate salinity induced toxic effects and improve the grain yield and zinc bio-fortification of wheat by improving antioxidant activities, photosynthetic performance, and accumulation of osmolytes and hormones - Chattha, Muhammad Umer; Amjad, Tahira; Khan, Imran; Nawaz, Muhammad; Ali, Muqarrab; Chattha, Muhammad Bilal; Ali, Hayssam M.; Ghareeb, Rehab Y.; Abdelsalam, Nader R.; Azmat, Saira; Barbanti, Lorenzo; Hassan, Muhammad Umair (Frontiers in Plant Science, 2022)
Salinity stress (SS) is a challenging abiotic stress that limits crop growth and productivity. Sustainable and cost effective methods are needed to improve crop production and decrease the deleterious impacts of SS. Zinc (Zn) nano-particles (NPs) have emerged as an important approach to regulating plant tolerance against SS. However, the mechanisms of SS tolerance mediated by Zn-NPs are not fully explained. Thus, this study was performed to explore the role of Zn-NPs (seed priming and foliar spray) in reducing the deleterious impacts of SS on wheat plants. The study comprised different SS levels: control, 6 and 12 dS m−1, and different Zn-NPs treatments: control, seed priming (40 ppm), foliar spray (20 ppm), and their combination. Salinity stress markedly reduced plant growth, biomass, and grain yield. This was associated with enhanced electrolyte leakage (EL), malondialdehyde (MDA), hydrogen peroxide (H2O2), sodium (Na), chloride (Cl) accumulation, reduced photosynthetic pigments, relative water contents (RWC), photosynthetic rate (Pn), transpiration rate (Tr), stomata conductance (Gs), water use efficiency (WUE), free amino acids (FAA), total soluble protein (TSP), indole acetic acid (IAA), gibberellic acid (GA), and nutrients (Ca, Mg, K, N, and P). However, the application of Zn-NPs significantly improved the yield of the wheat crop, which was associated with reduced abscisic acid (ABA), MDA, H2O2 concentration, and EL, owing to improved antioxidant activities, and an increase in RWC, Pn, Tr, WUE, and the accumulation of osmoregulating compounds (proline, soluble sugars, TSP, and FAA) and hormones (GA and IAA). Furthermore, Zn-NPs contrasted the salinity-induced uptake of toxic ions (Na and Cl) and increased the uptake of Ca, K, Mg, N, and P. Additionally, Zn-NPs application substantially increased the wheat grain Zn bio-fortification. Our results support previous findings on the role of Zn-NPs in wheat growth, yield, and grain Zn bio-fortification, demonstrating that beneficial effects are obtained under normal as well as adverse conditions, thanks to improved physiological activity and the accumulation of useful compounds. This sets the premise for general use of Zn-NPs in wheat, to which aim more experimental evidence is intensively being sought. Further studies are needed at the genomic, transcriptomic, proteomic, and metabolomic level to better acknowledge the mechanisms of general physiological enhancement observed with Zn-NPs application.